Effectiveness and safety of direct oral anticoagulants with antiplatelet agents in patients with venous thromboembolism: A multi‐database cohort study. Issue 1 (10th January 2022) - Douros, Antonios; Basedow, Frederike; Cui, Ying; Walker, Jochen; Enders, Dirk; Tagalakis, Vicky
Abstract: Background: Patients with venous thromboembolism (VTE) often have comorbidities that require use of antiplatelets. However, evidence on the effects of concomitant use of direct oral anticoagulants (DOACs) and antiplatelets in this high‐risk population is scarce. Our international, multi‐database cohort study assessed the real‐world effectiveness and safety of concomitant use of DOACs and antiplatelets among patients with VTE. Methods: We assembled two population‐based cohorts using administrative health care databases from Québec and Germany. We included patients with incident VTE who initiated treatment with a DOAC or a vitamin K antagonist (VKA), while being exposed to antiplatelets (acetylsalicylic acid, clopidogrel, ticagrelor, prasugrel, dipyridamole). The study period spanned from 2012 to 2016 (Québec) or 2019 (Germany). Concomitant use of DOACs and antiplatelets was compared with concomitant use of VKAs and antiplatelets, using inverse probability of treatment weighting to balance exposure groups. Cox proportional hazards models estimated site‐specific hazard ratios (HRs) and 95% confidence intervals (CIs) of major bleeding, all‐cause mortality (primary outcomes), and recurrent VTE (secondary outcome). Site‐specific estimates were meta‐analyzed using random‐effects models. Results: Overall, 4971 patients with VTE initiated concomitant use of a DOAC (n = 2289) or a VKA (n = 2682) and antiplatelets. Compared with concomitant use of VKAs and antiplatelets, concomitant use of DOACs and antiplatelets was associated with similar risks of major bleeding (HR, 0.81; 95% CI, 0.46‐1.45), all‐cause mortality (HR, 1.25; 95% CI, 0.87‐1.79), and recurrent VTE (HR, 0.96; 95% CI, 0.40‐2.27). Conclusions: Among patients with VTE using antiplatelets, there were no major differences in effectiveness and safety between DOACs and VKAs.